Rediseño organizacional para mejorar la comunicación interna del departamento de farmacia de la Corporación JASPHARM CIA. LTDA - Alvarado Palma, Amy Melissa (2023)
The present research aimed to study the importance of elaborating an organizational redesign that allows improving the internal communication of the staff in the Pharmacy Department of Jaspharm Corporation Ltd. The methodology used was descriptive with a mixed approach, along with the application of survey and interview techniques. The study population consisted of 33 employees. The results showed that 33.33% of them considered the bulletin board as completely disagreeable, while 39.39% agreed completely with face-to-face communication as an effective method. Additionally, 33.33% of the respondents deemed team meetings unproductive, and the manager also acknowledged deficiencies in communication. For these reasons, an organizational redesign proposal was developed to enhance internal communication, using the SMART methodology. This approach provides a structure that helps internal communication professionals establish relevant, achievable, and measurable objectives aligned with the organization's strategy and goals. In conclusion, it is crucial to implement this model as it reinforces productivity and makes internal communication more effective, transparent, and focused on tangible results, thereby contributing to a more cohesive work environment and a more successful organization as a whole.